Economic gangsters corruption, violence, and the poverty of nations - Fisman, Raymond; Miguel, Edward (Princeton University Press, 2008)
In Economic Gangsters, Raymond Fisman and Edward Miguel take readers into the secretive, chaotic, and brutal worlds inhabited by these lawless and violent thugs. Join these two sleuthing economists as they follow the foreign aid money trail into the grasping hands of corrupt governments and shady underworld characters. Spend time with ingenious black marketeers as they game the international system. Follow the steep rise and fall of stock prices of companies with unseemly connections to Indonesia's former dictator. See for yourself what rainfall has to do with witch killings in Tanzania--and more.